Application of Sarima Model in Load Forecasting in Hanoi City - Kien, Duong Trung; Huong, Phan Dieu; Minh, Nguyen Dat (International Journal of Energy Economics and Policy, 2023)
Many countries and researchers are interested in load forecasting due to its significance. The results of load forecasting are an indispensable basis for electricity planning and investment plan for the power system in the future. In addition, short-term load forecasting is also a mandatory requirement in proactively developing business and system operation plan of units in power sector. When the SARIMA(p,d,q)(P,D,Q)S model is used for load forecasting in Hanoi, the results ensure forecast accuracy, feasibility of available data as well as the software’s ease of use. SARIMA model can also be used in load forecasting in other provinces and cities in Vietnam or used for electricity forecasting. With the research sample from 2019 to 2021, the model SARIMA(0,1,6)(0.1,1)24 and (0,1,7)(0.1,1) 24 are used for short-term load forecasting in term of typical working day and day-off in Hanoi.